2022
DOI: 10.3390/microbiolres13030027
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Carbapenem-Resistant Gram-Negative Bacteria in Mizoram, Northeast India

Abstract: (Background) Numerous reports on carbapenem resistance in different parts of India have been published, yet there are insufficient studies on the prevalence of antibiotic resistance in the northeast region of the country. This study evaluated the emergence of carbapenem resistance in the clinical isolates collected in Mizoram. (Results) A total of 141 Gram-negative clinical isolates were collected from the two hospitals, including the Civil Hospital in Lunglei and the Synod Hospital in Aizawl. The isolates inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…This low level of resistance is similar to that from another study in China [40], where, of 100 E. coli strains isolated from different clinical samples, there were no isolates resistant to imipenem. In another study in Northeast India, the resistance levels to carbapenem were higher than in our findings, where, out of 62 E. coli isolates, 4 (6.4%) isolates were found to be carbapenem-resistant [53]. This variation in the level of resistance might be due to different treatment regimes followed in different hospitals and countries.…”
Section: Discussioncontrasting
confidence: 81%
“…This low level of resistance is similar to that from another study in China [40], where, of 100 E. coli strains isolated from different clinical samples, there were no isolates resistant to imipenem. In another study in Northeast India, the resistance levels to carbapenem were higher than in our findings, where, out of 62 E. coli isolates, 4 (6.4%) isolates were found to be carbapenem-resistant [53]. This variation in the level of resistance might be due to different treatment regimes followed in different hospitals and countries.…”
Section: Discussioncontrasting
confidence: 81%
“…28, 29 Several previous studies have demonstrated that the proportion of carbapenemase-producing isolates varies by location and study, ranging from 22% to 66%. 27, 30, 31 In contrast, characterisation of K. pneumoniae from non-clinical sources has been poorly documented apart form a few small localized studies. 32, 33 In the present study we detected phenotypic carbapenem resistance in 41.75% of clinical isolates during 2020 - 2022.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Several previous studies have demonstrated that the proportion of carbapenemase-producing isolates varies by location and study, ranging from 22% to 66%. 27,30,31 In contrast, characterisation of K.…”
Section: Discussionmentioning
confidence: 99%
“…Their work, apart from teaching, consisted of preaching the Gospel, planting churches as well as looking after these churches. 30 Often they would be travelling, preaching the Gospel in far off places. These first mission teachers were one of the most important foundations of the Church in Mizoram as well of the slowly changing society.…”
Section: Those Teachers Who Underwent the Teachers' Training Course T...mentioning
confidence: 99%
“…By 1927 Mizo mission teachers received training at the Mission station in Aizawl. 31 The training was a one-year course. The first of those trained Mizo teacher was Pasena.…”
Section: Those Teachers Who Underwent the Teachers' Training Course T...mentioning
confidence: 99%